Carboxymethyl cellulose from sugar beet pulp cellulose as a hydrophilic polymer in coating of apples - Togrul, H; Arslan, N (Springer India, 2005)
Paraffin wax (PW), bees wax (BW) and soybean oil, carboxymethyl cellulose (CMC, degree of substitution: 0.6670) from sugar beet pulp cellulose; Emulgin PE, triethanolamine, oleic acid and sodium oleate (SO) were used as hydrophobic phases, hydrophilic polymer and emulsifying agents (EA), respectively, in the coating of apples to extend storage life. Apples coated with different emulsions were stored at 25 degrees C and RH of 75%. Fruits were evaluated for water loss, pH, Soluble solids (SS), titratable acidity (TA), weight loss, and ascorbic acid. The modified drying models describing the storage time dependence of weight loss were fitted to the experimental data and the model parameters in equations were determined by multiple regression analysis. The two-term and polynomic models were found to satisfactorily describe water loss curves of apples with high correlation. The coatings decreased the SS, TA and ascorbic acid losses in comparison to the uncoated apples. Storage time was prolonged up to 34 days with lower weight loss by coating apple surfaces. The emulsion used soybean oil as hydrophobic phase, SO as EA, CMC from sugar beet pulp as hydrophilic polymer was suitable for the coating of apples.
Keywords: apples; storage; sugar beet pulp; cellulose; carboxymethyl cellulose; coating